1893 Fla. Laws 52 §2 - (:unkn) unknown (General Publisher, 1893)
Enhanced the sentence of anyone arrest for a criminal offense or breach of the public peace while carrying any slung shot, metallic knuckles, billies, fire-arms, or other dangerous weapon. Punishable by imprisonment of three months, or by fine not exceeding one hundred dollars, or both.
--
Keywords: CARRY - INTENT TO COMMIT CRIME